Exploring the Emotional Breastfeeding Experience of First-Time Mothers: Implications for Healthcare Support - Maria Lorella Giannì; Maria Lorella Giannì; Marta Lanzani; Alessandra Consales; Alessandra Consales; Giovanna Bestetti; Lorenzo Colombo; Maria Enrica Bettinelli; Laura Plevani; Daniela Morniroli; Gabriele Sorrentino; Elena Bezze; et al. (Frontiers Media S.A., 2020)
Background: Among breastfeeding determinants, the unique emotional breastfeeding experience has been poorly explored. The present study aimed to investigate the emotional breastfeeding experience in a cohort of first-time mothers.Materials and methods: We conducted a prospective observational study that enrolled primiparas having delivered singleton healthy term newborns, and exclusively breastfeeding at hospital discharge. At 3 months post-delivery mothers accessed an online questionnaire investigating their emotional breastfeeding experience. The chi-squared test was used to assess the association between the feelings experienced during breastfeeding and feeding outcomes at 3 months.Results: Out of the 421 enrolled mothers, 273 (65%) completed the questionnaire. At 3 months post-delivery exclusive breastfeeding was reported by a 66% of mothers, a 19% reported complementary feeding, and a 15% of mothers reported exclusive formula feeding. Breastfeeding experience was described as positive by 62% of mothers although breastfeeding difficulties were reported by 80% of the mothers. The mothers that had experienced fear, sadness, anger or concern during breastfeeding showed a significant higher exclusive formula feeding rate at 3 months post-delivery than those who did not (25.5 vs. 12.8%, p = 0.021; 28.6 vs. 13.4%, p = 0.02; 40 vs. 13.4%, p = 0.005; 20.5 vs. 11.8%, p = 0.049, respectively). An 85% of mothers stated that their breastfeeding experience was different from what they would have expected, blaming for this discrepancy the occurrence of difficulties during breastfeeding and the complexity of breastfeeding itself (50%), pain experience (8%), being dependent from the baby (6%), and breastfeeding failure (11%). A total of 25% of mothers, however, reported they found breastfeeding to be a much more positive experience than what they had expected.Conclusion: Breastfeeding care should include a tailored emotional support of first time-mothers in addition to the implementation of their breastfeeding knowledge and skills.